2023
DOI: 10.3390/ijerph20115947
|View full text |Cite
|
Sign up to set email alerts
|

The Professional Identity of Social Workers in Mental Health Services: A Scoping Review

Abstract: Recent research into the role of mental health social work has identified a need for increased critical engagement with accounts of professional role and identity. Notably, a number of studies have found that social workers struggle to articulate their role within mental health teams and services. This study aimed to identify the ways in which social workers in mental health settings defined their professional identity and role. An international scoping review utilizing Arksey and O’Malley’s method was conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 74 publications
(162 reference statements)
0
2
0
Order By: Relevance
“…Professional identity in social work remains a very important and yet highly contested issue (Webb, 2017). Its importance lies in the constant need for social workers to define and assert themselves professionally, particularly for those who practice in multidisciplinary settings (Bark et al, 2023). Although much scholarly attention has been paid to the concept, it remains a very complex process, which as Fran Wiles (2013, p. 864) insists, extends beyond 'adopting certain traits or values, or even demonstrating competence.'…”
Section: Introductionmentioning
confidence: 99%
“…Professional identity in social work remains a very important and yet highly contested issue (Webb, 2017). Its importance lies in the constant need for social workers to define and assert themselves professionally, particularly for those who practice in multidisciplinary settings (Bark et al, 2023). Although much scholarly attention has been paid to the concept, it remains a very complex process, which as Fran Wiles (2013, p. 864) insists, extends beyond 'adopting certain traits or values, or even demonstrating competence.'…”
Section: Introductionmentioning
confidence: 99%
“…Research has found, for example, that social workers in multidisciplinary mental health services report marginalisation of their professional contributions, with social approaches to mental health considered subordinate to medical models of understanding mental health and its management 56. Research has also found the language of “recovery” to be contested in mental health services.…”
mentioning
confidence: 99%